Happiness: A Novel Outcome Measure in Stroke? - Wijeratne T; Sales C; Wijeratne C; Jakovljevic M (Dove Medical Press, 2021)
Tissa Wijeratne,1– 4 Carmela Sales,1,2 Chanith Wijeratne,5 Mihajlo Jakovljevic6,7 1Department of Neurology, Sunshine Hospital, Western Health, St. Albans, VIC, Australia; 2Department of Psychology & Counselling, School of Psychology & Public Health, La Trobe University, Bundoora, VIC, Australia; 3Department of Medicine, AIMSS, Melbourne Medical School, University of Melbourne, Sunshine Hospital, St Albans, VIC, Australia; 4Department of Medicine, University of Rajarata, Salypura, Anuradhapuraya, Sri Lanka; 5Monash Medical School, Monash University, Clayton, VIC, Australia; 6Department Global Health Economics & Policy, University of Kragujevac Faculty of Medical Sciences, Kragujevac, Serbia; 7Institute of Comparative Economic Studies, Hosei University Faculty of Economics, Tokyo, JapanCorrespondence: Tissa Wijeratne Email Tissa.wijeratne@wh.org.auAbstract: In this narrated review, we draw attention to the use of happiness as a novel outcome measure in clinical research studies regarding patients with stroke. Commonly used outcome measures in clinical trials in stroke rehabilitation include the modified Rankin Score (mRS), Functional Impairment Measures (FIM), Barthel Index and quality of life (QoL). Despite being a part of QoL, happiness is arguably a significant construct on its own. While QoL assesses perceptions of various extrinsic aspects of life, happiness may be used as a measure of subjective enjoyment of life after an illness. We review the literature discussing the use of happiness as a formal outcome measure in stroke care and subacute and long-term stroke rehabilitation. Ultimately we recommend the wider use of happiness as an outcome measure where appropriate in these settings.Keywords: stroke, quality of life, happiness, brain health